The Multipartite Mitochondrial Genome of Marama (Tylosema esculentum) - Li, Jin; Cullis, Christopher (Frontiers in Plant Science, 2021)
Tylosema esculentum (marama bean), a wild legume from tropical Africa, has long been considered as a potential crop for local farmers due to its rich nutritional value. Genomics research of marama is indispensable for its domestication and varietal improvement. The chloroplast genome of marama has been sequenced and assembled previously using a hybrid approach based on both Illumina and PacBio data. In this study, a similar method was used to assemble the mitochondrial genome of marama. The mitochondrial genome of the experimental individual has been confirmed to have at least two different structures, five small circular molecules or two long rings. The two structures are believed to be interchangeable by recombination on the 4 pairs of long repeats (>1kb). The total length of marama mitogenome is 399,572 bp. A 9,798 bp DNA fragment has been found that is homologous to the chloroplast genome of marama, accounting for 2.5% of the mitogenome. In Fabaceae family, the mitogenome of Millettia pinnata is highly similar to marama with respect to both the genes present and the total size. Certain genes including cox2, rpl10, rps1 and sdh4 have been lost during the evolution of angiosperms and are absent in the mitogenomes of some legumes. However, these remain intact and functional in marama. Another set of genes, rpl2, rps2, rps7, rps11, rps13 and rps19 are either absent or present as pseudogenes in the mitogenome of marama.